2021
DOI: 10.1111/jcal.12530
|View full text |Cite
|
Sign up to set email alerts
|

Attention‐driven read‐aloud technology increases reading comprehension in children with reading disabilities

Abstract: The paper presents the design of an assistive reading tool that integrates read-aloud technology with eye-tracking to regulate the speed of reading and support struggling readers in following the text while listening to it. The paper describes the design rationale of this approach, following the theory of auditory-visual integration, in terms of an automatic self-adaptable technique based on the reader's gaze that provides an individualized interaction experience. This tool has been assessed in a controlled ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…These studies unanimously agree on the negative impact of the COVID-19 pandemic on the health and well-being of children with disabilities and their families, especially those with developmental dyslexia, and they recommend providing and supporting conscious post-disaster trauma treatment practices. Several researchers (Buele et al, 2020 ; Schiavo et al, 2021 ; Aldabaybah & Jusoh, 2018 ) have stated that these practices can be introduced intensively and consciously by transferring traditional learning strategies to applications and digital environments. Considering the features of these applications that support audiovisual learning (McNicholl et al, 2020 ; Schmitt et al, 2019 ), this study was conducted to employ the potential features and characteristics of AT applications to support students with dyslexia in developing their reading skills by improving VP and PhP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies unanimously agree on the negative impact of the COVID-19 pandemic on the health and well-being of children with disabilities and their families, especially those with developmental dyslexia, and they recommend providing and supporting conscious post-disaster trauma treatment practices. Several researchers (Buele et al, 2020 ; Schiavo et al, 2021 ; Aldabaybah & Jusoh, 2018 ) have stated that these practices can be introduced intensively and consciously by transferring traditional learning strategies to applications and digital environments. Considering the features of these applications that support audiovisual learning (McNicholl et al, 2020 ; Schmitt et al, 2019 ), this study was conducted to employ the potential features and characteristics of AT applications to support students with dyslexia in developing their reading skills by improving VP and PhP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A further advance has been made with the introduction of specific and sophisticated tools aimed at increasing the impaired skills. For example, in the work of [59], using a computer platform equipped with speech synthesis and eye tracking was a great boost to the comprehension of a text by dyslexic subjects. Several works have explored the use of AI, demonstrating that it is likely to be one of the most effective instruments to face the problem.…”
Section: Related Workmentioning
confidence: 99%
“…This fact highlights the necessity to combine both supporting methodologies in order to be capable of helping dyslexic students during their academic career. Conversely, the vast majority of approaches proposed until now [56][57][58][59][60][61][62][63][64][65] have only taken into account digital tools, neglecting to also create, in parallel, a list of the best practices to be followed to provide support to dyslexic students. The supporting strategies that obtained the highest scores are taking pauses during lessons, hosting lessons online, repeating the studied material and making the program and the slides of the course available, which are considered useful by about 96 to 99% of the participants in the questionnaire.…”
Section: Supporting Toolmentioning
confidence: 99%
“…Despite increasing evidence on the benefit of text-to-speech on reading comprehension, however, the underlying cognitive mechanisms supported by such technology remain largely unknown (Schiavo et al, 2021). According to the cognitive theory of multimedia learning (Mayer, 2014), for instance, integrating cross-channel representations (e.g., auditory/visual) of the same stimulus (e.g., a written word) is supposed to help the reader overcome the capacity limitations of the cognitive system when accessing material to be learned.…”
Section: Mw and The Impact Of Different Reading Materialsmentioning
confidence: 99%
“…In this view, multimodal (i.e., auditory-visual) text presentation through text-tospeech software may help readers with dyslexia mitigate visual distraction due to their high sensitivity to crowding, which is supposed to impair letter identification in the periphery, thus reducing reading speed by limiting the number of letters able to be perceived at a glance (Pelli et al, 2007;Schneps et al, 2019). In addition, it has been recently suggested that the ability of text-to-speech software to highlight words can also improve verbal and visual information processing in working memory, increasing the mental resources that can be devoted to comprehension (Schiavo et al, 2021).…”
Section: Mw and The Impact Of Different Reading Materialsmentioning
confidence: 99%